ASSESSING THE ROLE OF TECHNOLOGICAL INNOVATION IN THE RELATIONSHIP BETWEEN FDI AND ENVIRONMENTAL DEGRADATION - Sher, Fazal; Ali, Naveed; Hayat, Umar; Manan, Samia (ACADEMIA International Journal for Social Sciences, 2025)
The present study explores the interactive role technological innovations with foreign direct investment in influencing environmental degradation, using panel dataset of Next eleven countries, ranging from 1990 to 2023. A series of econometric techniques are used to investigate the dynamics between FDI and environmental degradation. The study, in the outset tested the cross-sectional dependence among the countries to capture the potential interdependencies in their growth and investment trends, followed by slope heterogeneity test and then panel unit root test, all are conducted to ensure the reliability of the analyses. The Augmented Mean Group (AMG) technique is then applied to explore the possible interactive role of TI with FDI in influencing environment degradation.  Moreover, to verify the robustness of our panel AMG estimation results, the CCEMG technique is used. Our results suggest that technological innovation play significant interactive role with FDI in alleviating the adverse outcomes of FDI on the environment.  In particular, this factor helps reduce territory-based carbon emissions linked with FDI inflows, indicating a potential pathway for fostering sustainable development. This study contributes to the existing literature by highlighting the importance of integrating complementarity factors in policymaking, encouraging developing nations to capitalize this synergy to balance economic growth with environmental preservation. Policymakers can leverage this insight to design targeted strategies that effectively reduce environmental degradation.